An analysis of illocutionary acts in a fantasy movie - Siti Sarah Fitriani; Diana Achmad; Fitria Rasmita (Studies in English Language and Education, 2020)
This study aims to find out the types and the most dominant illocutionary acts used by the main character in a fantasy movie, ‘Harry Potter and the Chamber of Secret’. A descriptive qualitative study was done by observing the utterances spoken by the main character in the movie. The spoken utterances were then analysed based on the types of illocutionary acts, namely: representative, directive, commissive, expressive and declarative.  The results of the study showed that out of the five, only four types of illocutionary acts were found in the movie, they are representative, directive, expressive, and commissive. The most frequently illocutionary act used is directive (47.64%), while the least frequently used is commissive (4.19%). The directive forces used by the main character are varied. Directives are used get the hearers to do something, where in the movie, he often used asking and ordering. Meanwhile, declarative is not employed by the main character since performing declarative act needs authorities and status; this act is used to change the world through utterances. But the main character in this movie do not have any certain status or authority in any position at the magic school he attended, he is a student, still new with the magic world and do not have much power. This is why declarative was not found in the utterances of the main character.